Risk factors for 90-day all-cause mortality in post-operative central nervous system infections (PCNSIs): A retrospective study of 99 patients in China. Issue 52 (30th December 2022) - Zhao, Yanan; Deng, Wenjing; Teng, Junfang; Xu, Yafei; Pan, Pengwei; Jin, Di
Abstract : Post-operative central nervous system infections (PCNSIs) are serious complications of craniotomy. Many factors, including patient-related, surgical, and postoperative factors, affect the survival of patients with PCNSIs. Timely and effective implementation of antibiotics targeting pathogenic bacteria is crucial to reduce mortality. Metagenomic next-generation sequencing (mNGS) has been used successfully to detect pathogens associated with infectious diseases. This study was designed to evaluate the factors influencing mortality and to explore the application value of mNGS in patients with PCNSIs. We conducted a retrospective study of patients with PCNSIs in our unit from 1/12/2019 to 28/2/2021. Clinical data, cerebrospinal fluid (CSF) parameters, surgical information, and mNGS results were collected. Follow-up telephone calls were made in June 2021 for 90 days survival after discharge. 99 patients were enrolled, and the overall mortality rate was 36.4% (36/99). Kaplan–Meier survival analysis suggested that the risk factors for poor prognosis included age ≥ 53 years, Glasgow Coma scale (GCS) score ≤ 8, CSF/blood glucose ratio (C/B-Glu) ≤ 0.23, 2 or more operations, mechanical ventilation (MV), and non-mNGS test. MV and poor wound healing were independent risk factors for 90 day mortality according to the multivariate Cox proportional hazards model (OR = 6.136, P = .017, OR = 2.260, P = .035, respectively). Among the enrolled patients, causative pathogens were identified in 37. Gram-negative pathogens were found in 22 (59.5%) patients, and the remaining 15 (40.5%) were Gram-positive pathogens. Univariate analysis showed that white cell count and protein and lactate levels in the CSF of the Gram-negative group were higher than those of the Gram-positive group ( P < .05). mNGS and conventional microbiological culture were tested in 34 patients, and the positive detection rate of mNGS was 52.9%, which was significantly higher than that of microbiological culture (52.9% vs 26.5%, χ 2 = 4.54, P = .033). The mortality rate of PCNSIs is high, and patients with MV and poor wound healing have a higher mortality risk. Gram-negative pathogens were the predominant pathogens in the patients with PCNSIs. mNGS testing has higher sensitivity and has the potential to reduce the risk of mortality in patients with PCNSIs.